2021
DOI: 10.1177/21582440211021598
|View full text |Cite
|
Sign up to set email alerts
|

Do ESG Endeavors Assist Firms in Achieving Superior Financial Performance? A Case of 100 Best Corporate Citizens

Abstract: Increasing interest in sustainability performance (environmental, social, and governance pillar performance [ESGP]) and corporate financial performance (CFP) is noteworthy. However, we do not find any all-inclusive study that employs both individual components of environmental, social, and governance pillars (ESG) as well as the cumulative ESG score on both the accounting and market performance of firms. Furthermore, we do not find any study that puts forth “best practices” in the ESGP-CFP nexus. Therefore, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 83 publications
2
35
1
3
Order By: Relevance
“…Finally, the effect of ESG on TQ was also negative. This is further supported by evidence of a non-significant and negative correlation in relation to market performance using TQ (Landi and Sciarelli, 2019; Qureshi et al. , 2021).…”
Section: Findings and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Finally, the effect of ESG on TQ was also negative. This is further supported by evidence of a non-significant and negative correlation in relation to market performance using TQ (Landi and Sciarelli, 2019; Qureshi et al. , 2021).…”
Section: Findings and Discussionmentioning
confidence: 66%
“…Finally, the effect of ESG on TQ was also negative. This is further supported by evidence of a non-significant and negative correlation in relation to market performance using TQ (Landi and Sciarelli, 2019;Qureshi et al, 2021). Some studies have attributed this to the increased costs associated with ESG, which, in turn, lower market value (Marsat and Williams, 2011).…”
Section: Sustainabilitymentioning
confidence: 80%
“…Conversely, the trade‐off theory believes there is a negative link between ESG and FV. It suggests that ESG investments and other business opportunities must compete for the same available resources (Azmi et al, 2021), and that funds spent on ESG activities (such as investment in pollution reduction, donations, and community sponsorships) meaninglessly increase operating costs, resulting in reduced profitability (Azeem Qureshi et al, 2021) and reduced competitive advantage (El Khoury et al, 2021; Galant & Cadez, 2017).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Empirically, the literature has produced mixed results when examining the relationship between CSR and FP (Gillan et al, 2021). The majority of the literature has reported a positive effect of CSR on FP (Brogi and Lagasio, 2019;Long et al, 2020;Okafor et al, 2021;Qureshi et al, 2021). In an extensive review of more than 250 academic studies, Margolis et al (2009) concluded that the effect of CSR on FP is positive.…”
Section: Literature Reviewmentioning
confidence: 99%